Ayurvedic Management of Dry Eye (AYUSHDHARA, 2024)
Dry eye is a multifactorial illness of the tears and ocular surface, dry eye causes pain, disruptions to vision, instability in the tear film, and maybe even damage to the ocular surface. Tear secretion gives the corneal epithelium oxygen and continuously lubricates and moisturises the ocular surface. Dry eyes result from a disruption in regular tear production. Local, systematic and environmental factors play a major role in pathogenesis. Often exacerbated by smoke, wind, heat, low humidity or prolonged use of the eye. One of the most common disorders affecting the eyes is dry eye, affecting millions of people globally. The worldwide prevalence ranges from 5% to 50%, depending on the geographic region, Prevalence rate in India is higher than the global prevalence and ranges from 18.4% to 54.3%. Shushkaksipaka is one among Sarvagata netra rogas disease affecting all parts of the eye can be symptomatically correlated with dry eye. Vata and Pitta vitiation as per Ayurvedic view point are the major contributing pathological factor in its manifestation. This is a single case study of Shushkakshipaka treated with Deepana, Pachana, Kosta Shodhana, followed by 2 sittings of Ksheera Saindhava Prakshalana and Suntyadi Anjana and Anu taila Pratimarsha Nasya. At the end of the study improvement in foreign body sensation and itching. Patient got very significant result is being discussed here.